2008
DOI: 10.1128/jb.01688-07
|View full text |Cite
|
Sign up to set email alerts
|

Moraxella catarrhalisSynthesizes an Autotransporter That Is an Acid Phosphatase

Abstract: Moraxella catarrhalis O35E was shown to synthesize a 105-kDa protein that has similarity to both acid phosphatases and autotransporters. The N-terminal portion of the M. catarrhalis acid phosphatase A (MapA) was most similar (the BLAST probability score was 10 Initially thought to be a harmless commensal organism, Moraxella catarrhalis has gradually gained repute as an etiologic agent of at least two significant diseases in humans. This gram-negative, unencapsulated bacterium has been shown to colonize the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…Multiple mechanisms are available to anchor a given polypeptide to a bacterial membrane. For example, Hoopman et al have demonstrated the existence of an acid phosphatase domain present as the N-terminal portion of the Moraxella catarrahlis MapA membrane-associated autotransporter protein (14). Irrespective of its anchoring mechanism, the preponderance of our data suggests CppA membrane association.…”
Section: Discussionmentioning
confidence: 45%
“…Multiple mechanisms are available to anchor a given polypeptide to a bacterial membrane. For example, Hoopman et al have demonstrated the existence of an acid phosphatase domain present as the N-terminal portion of the Moraxella catarrahlis MapA membrane-associated autotransporter protein (14). Irrespective of its anchoring mechanism, the preponderance of our data suggests CppA membrane association.…”
Section: Discussionmentioning
confidence: 45%
“…A DNA: DNA hybridization study was performed to determine the extent to which these ATCC 43617-derived probes would bind O35E-derived cDNAs. For this purpose, the O35E⌬mapA mutant (29) was used as a representative O35E-derived strain because this strain was a potential candidate for use in competitive index experiments in the chinchilla model. This O35E⌬mapA mutant differs from the O35E.118.rpsL strain only by the presence of a spectinomycin resistance cartridge inserted into its mapA gene (29) and the absence of the single nucleotide change in the rpsL gene.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the O35E⌬mapA mutant (29) was used as a representative O35E-derived strain because this strain was a potential candidate for use in competitive index experiments in the chinchilla model. This O35E⌬mapA mutant differs from the O35E.118.rpsL strain only by the presence of a spectinomycin resistance cartridge inserted into its mapA gene (29) and the absence of the single nucleotide change in the rpsL gene. When probed in DNA:DNA hybridization experiments with chromosomal DNA fragments from the homologous ATCC 43617 strain, a hybridization frequency of 99.1% was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Translocator, or beta, domains of autotransporters are capable of transporting any heterologous passenger domain to the outer membrane (21,24). To determine if the C-terminal regions of AipA and TaaP function as true translocators, we translationally fused the regions corresponding to the beta domains of AipA (AipA ␤ ) and TaaP (TaaP ␤ ) individually to the passenger domain of Pta (Pta␣) (Fig.…”
Section: Resultsmentioning
confidence: 99%